2010
DOI: 10.1002/marc.200900534
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Properties of Microgel‐PVP Composite Nanofibers Made by Electrospinning

Abstract: The absorption and desorption of water, as well as the retention of certain molecules within a polymeric network, have special interest in a wide range of applications, including drug delivery, biosensing, chemical separation, catalysis, and optics. In this communication, we report the encapsulation by electrospinning of poly(N-isopropylacrylamide)-based monodisperse microgels within microfibers of crosslinked poly(vinylpyrrolidone), which is a hydrogel itself, up to concentrations of 40 wt.-% of the microgels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…After decades of research, polymeric microgels have demonstrated to be versatile systems with potential applications as diverse as industrial applications as paints, ink jets printing, separation [3] and biomedical applications such as drug delivery systems [4,5], biomimicking artificial synovial fluids [6], tissue mimicking [7] and injectable 3D cell scaffolds [8]. Besides the mentioned advanced applications, microgel can be used as building blocks to create structures such as colloidal crystals, films and gels in the macroscopic scale [9,10,11,12], but also as active sites incorporated within functional polymer matrices so that the design of tailored multifunctional materials can be obtained [13,14]. Following this idea, in a recent work we used thermoresponsive poly( N -isopropylacrylamide), (PNIPAM) based microgels as active sites encapsulated into polymeric nanofiber as a first approach toward the design of new active wound dressings [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…After decades of research, polymeric microgels have demonstrated to be versatile systems with potential applications as diverse as industrial applications as paints, ink jets printing, separation [3] and biomedical applications such as drug delivery systems [4,5], biomimicking artificial synovial fluids [6], tissue mimicking [7] and injectable 3D cell scaffolds [8]. Besides the mentioned advanced applications, microgel can be used as building blocks to create structures such as colloidal crystals, films and gels in the macroscopic scale [9,10,11,12], but also as active sites incorporated within functional polymer matrices so that the design of tailored multifunctional materials can be obtained [13,14]. Following this idea, in a recent work we used thermoresponsive poly( N -isopropylacrylamide), (PNIPAM) based microgels as active sites encapsulated into polymeric nanofiber as a first approach toward the design of new active wound dressings [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds of hybrids or composites, which are made of electrospun fibers and gel, may have unexpected influence on cell behaviors . Microgel electrospinning is a technology for fabricating a composite material based on microgel particles trapped inside nanofibers . A biomimetic bilayer sheath composed of microgel HA/PCL fibrous membrane as the inner layer and PCL fibrous as the outer layer was prepared via sequential and microgel electrospinning .…”
Section: Animal Polysaccharides For Electrospinning and Their Potentimentioning
confidence: 99%
“…These smart materials have received much attention owing to their environmentally tunable sizes and potential applications, such as chemical separation, catalysis, sensors, enzyme immobilization, drug delivery systems, biomimicking artificial synovial fluids, tissue mimicking, and injectable 3D cell scaffolds, among others [3,4,5,6,7,8]. Besides the mentioned advanced applications, microgels are used as building blocks to create structures such as colloidal crystals, films, and gels in the macroscopic scale [9,10,11,12], and more recently as active sites confined within electrospun polymer fibers toward the design of tailored multifunctional stimuli-responsive advanced materials [13,14,15,16]. In our previous works, we first developed poly(acrylamide- co- acrylic acid) microgels featured with the ability to swell upon heating, thus showing a positive thermosensitivity and an upper critical solution temperature-like (UCST) volume phase transition temperature [17,18].…”
Section: Introductionmentioning
confidence: 99%